Frontline Heroes: Challenges And Professional Responsibilities Of Paramedics In The Saudi Red Crescent Authority (The Review of Diabetic Studies, 2025)
Paramedics working within the Saudi Red Crescent Authority (SRCA) are central to Saudi Arabia’s prehospital emergency medical services (EMS). They deliver rapid assessment, triage, stabilization, and transport in time‑critical situations, often operating in unpredictable environments such as highways, remote areas, industrial sites, and mass gatherings. This paper examines the professional responsibilities of SRCA paramedics—clinical, ethical, legal, communication, and systems‑based duties—alongside the major occupational and organizational challenges that shape their daily practice. Key challenges include high call volumes, shift work and fatigue, exposure to traumatic events, workplace violence, road and scene hazards, infection risks, documentation burdens, variable access to advanced resources, and the need for continuous competency development amid evolving protocols. The analysis highlights how these stressors can influence clinical decision‑making, safety, retention, and patient outcomes. Finally, the paper proposes practical, evidence‑informed strategies to strengthen paramedic support: structured mental health services, fatigue risk management, high‑reliability safety culture, advanced training and simulation, improved interagency coordination, technology‑enabled decision support, and clear career pathways. Strengthening SRCA paramedic resilience and performance aligns directly with Saudi Vision 2030’s health sector transformation goals by improving emergency preparedness, response quality, and population health security.